Eukaryotic diversity and trophic levels inside the tank bromeliad Pseudalcantarea grandis in a dry area as detected by eDNA metabarcoding - José Alan Herrera-García; Mahinda Martinez; Pilar Zamora-Tavares; Ofelia Vargas; Luis Hernández-Sandoval (Revista Mexicana de Biodiversidad)
Some bromeliads form a compact rosette that accumulates detritus and water, known as phytotelma. The phytotelma is a lentic ephemeral aquatic environment that forms diverse communities with complex trophic levels. Pseudalcantarea grandis, a saxicolous plant, forms a phytotelma. To understand the importance of P. grandis as a eukaryotic diversity reservoir in arid zones, we collected water samples from 5 plants growing in a dry canyon in Zimapán, Hidalgo, Mexico. We analyzed them through metabarcoding of the ITS1 (Internal Transcribed Spacer) and the partial 5.8S gene. We used the Ion Torrent PGM platform for the sequencing, and the taxonomic assignation for the amplicons was made with BLAST in Genbank at NCBI. We found 26 phyla and 543 genera, 80% of which belonged to Ascomycota, Basidiomycota, Blastocladiomycota Chytridiomycota, Glomeromycota, Mucoromycota, and Zoopagomycota phyla. The remaining 20% was composed of 19 phyla belonging to other kingdoms. Photosynthetic organisms were represented by the phyla Bacillariophyta, Charophyta, Chlorophyta, and Ochrophyta. The vascular plants do not live in the tank but constitute the debris sustaining the large number of decomposers. The trophic levels in the tank were detritus, micro- and macro-decomposers, filter feeders, photosynthesizers, micro-predators, aquatic volume predators, surface predators, and parasites.